European Students in the Bologna Process - Klemencic, Manja (International Higher Education, 2008)
One of the student organizations in Europe has played a particularly visible role in the Bologna process. ESIB (the National Unions of Students in Europe), which has been renamed ESU (European Students' Union [www.esib.org]), has taken active part in the Bologna process, ensuring that student interests were reflected in its policies. At the same time, ESU used the process to upgrade its visibility and role in European higher education policymaking in general. The Bologna process has thus unexpectedly also created circumstances that led to cooperation among the student unions and strengthened their resolve to empower ESIB to represent them on the European level.